2008
DOI: 10.1017/s1751731108001572
|View full text |Cite
|
Sign up to set email alerts
|

Osmolarity and composition of cell culture media affect further development and survival in zebrafish embryos

Abstract: With the aim of carrying out chimaerism and somatic cell-midblastula transition (MBT) embryos co-culture experiments in freshwater fish species, we evaluated the effect of osmolarity and composition of two media commonly used in cell fish culture on MBT zebrafish embryos and their further development and survival. To this end, wild zebrafish dechorionated embryos in midblastula stage were cultured for 6 days (Experiment 1: 189 embryos) or 1 h (Experiment 2: 150 embryos) in three different media: Hanks' 10% (H-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…However, citric acid at a concentration of only 5% significantly altered the osmolarity of the tank water, which represents an almost 10-fold change. This value could be potentially damaging; however, a study by Perez-Camps and Garcia-Ximenez (2008) reported that the survival rate was 100% when zebrafish larvae were kept for 48 h at 315 mOsm and that larvae kept for 1 h at the same osmolarity had a survival rate of 100% after 6 days. Thus, further studies are needed to clarify the impact of osmolarity both in isolation and combined with pH.…”
Section: Experiments 1: Impact Of Noxious Chemicals On Larval Behaviourmentioning
confidence: 99%
“…However, citric acid at a concentration of only 5% significantly altered the osmolarity of the tank water, which represents an almost 10-fold change. This value could be potentially damaging; however, a study by Perez-Camps and Garcia-Ximenez (2008) reported that the survival rate was 100% when zebrafish larvae were kept for 48 h at 315 mOsm and that larvae kept for 1 h at the same osmolarity had a survival rate of 100% after 6 days. Thus, further studies are needed to clarify the impact of osmolarity both in isolation and combined with pH.…”
Section: Experiments 1: Impact Of Noxious Chemicals On Larval Behaviourmentioning
confidence: 99%
“…Moreover, the fact of keeping the embryos in HBSS only during micromanipulation and transferring them to H10 medium for incubation (with the consequent sharp osmolarity change), did not prevent embryos continuing their development without any delay (Pérez-Camps and García-Ximénez, 2008). So, these results are of interest to take into account in future chimaerism works.…”
Section: Handling Medium Osmolarity In Chimaerism Experiments Affementioning
confidence: 97%
“…The other drop was the handling drop, which means the place where the chimaerism was performed and it was composed by HC medium (Pérez-Camps and García-Ximénez, 2008). The number of injected cells per recipient embryo ranged from 50 to 100 cells and they were deposited into the animal pole as was described by Lin et al (1992).…”
Section: Chimaerism Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…However, it was proved that MBT embryos could support high osmolarities (300 mOSm) for 1h without further damage in the development (Pérez-Camps and García-Ximénez, 2008). In addition, Francisco-Simao and Cardona-Costa et al (2009) reported that the low osmolarity commonly used in chimaerism experiments does not affect the viability of the transplanted cells, but that it affects embryonic survival.…”
Section: Recipient Embryomentioning
confidence: 99%